A TURKIC ALLIANCE: POSSIBLE ALTERNATIVE TO TURKEY’S UNREALIZED EU MEMBERSHIP? - VARBANETS, Pavel (CENTRAL ASIA AND THE CAUCASUS, 2009)
For many years now the Turkish political elite has been convinced that the country’s EU membership would be the logical conclusion to the modernization processes launched by Kemal Atatürk. Until recently this trend was vehemently opposed only by the extreme right nationalists, who had no real popular support inside the country. The Turkish Islamists, on the other hand, have not merely moved away from their traditional opposition to Europe, they have grasped the advantages of European integration that promised to relieve them of the rigid control imposed by the military.1 Its firm dedication to EU membership has been keeping the ruling pro-Islamic Justice and Development Party in power for over six years.European integration remains the pivot of the country’s foreign policy course. The recent decisions of France and Austria to put the Turkish question up for discussion at national referendums nearly buried Turkey’s prospects for EU membership. Sooner or later the Turks will have to accept the fact that they should look for their foreign policy pivots elsewhere. Close cultural and historical ties and common economic interests make the Turkic world a logical choice.On 4 October, 2005 Turkey and the European Union began their official talks on Turkey’s EU membership. Today, more than three years later the Turkish leaders are still resolved to meet all the requirements. Recently the Foreign Ministry of this country said that EU membership was a strategic aim. “We are fully determined to implement the political and economic criteria.”2 With each passing year, however, it is becoming increasingly clear that EU membership will remain forever outside Turkey’s reach for cultural, economic and political reasons. On top of this, the recent eastward expansion of the European Union has already created numerous domestic problems for it. On the whole Turkey is facing two groups of problems that keep it outside the EU. All candidates are expected, first, to modernize their economic, political, and legal systems to adjust them to the EU membership criteria in order to minimize the cost and risks for the European Union.3 These criteria were laid down at the 1993 European Council in Copenhagen and the 1995 European Council in Essen. Some of the key EU integration criteria were also entered into the 1995 White Book of the European Commission. A country may claim EU membership only when it has attained the standards.he second group of factors is of a purely subjective nature: the civilizational, cultural, historical, and geographic specifics and the complexity of the EU domestic situation. While the first group of problems can be removed through gradual and consistent adaptation to the EU criteria, the candidate-country is powerless to do anything about the second group.